PCIT-Health: Preventing Childhood Obesity by Strengthening the Parent–Child Relationship. Issue 2 (May 2022) - Niec, Larissa N.; Todd, Mitchell; Brodd, Irene; Domoff, Sarah E.
Abstract: Childhood obesity is a costly, yet preventable, public health concern. Strengthening the parent–child relationship and teaching parents strategies to manage children's general and health-related behaviors has the potential to reduce childhood obesity risk. Selective prevention interventions may help parents of young children establish positive parenting and feeding practices to actively reduce risk factors. We review the existing literature on childhood obesity interventions and describe an adaptation to a behavioral parent training program—parent–child interaction therapy (PCIT)—to address children's behaviors in obesity-salient (e.g., mealtime, screen time, bedtime) contexts. In a case example, we describe how PCIT-Health can be effectively implemented. Highlights: Childhood obesity is a serious public health concern, related to numerous negative health outcomes. The quality of the parent–child relationship contributes to childhood obesity risk. Excessive screen use in children increases obesity risk Successful obesity prevention models should include intervention at the parent–child dyad level. PCIT-Health is a promising intervention to reduce childhood obesity risk.